An unbiased genome-wide analysis of zinc-finger nuclease specificity - Gabriel, Richard; Lombardo, Angelo; Arens, Anne; Miller, Jeffrey C.; Genovese, Pietro; Käppel, Christine; Nowrouzi, Ali; Bartholomä, Cynthia C.; Wang, Jianbin; Friedman, Geoffrey; Holmes, Michael C.; Gregory, Philip D.; et al. (Nature biotechnology, 2011)
Zinc-finger nucleases allow targeted genetic modification at loci chosen by the investigator, but the extent of their off-target activity—which could be toxic to cells—has not been evaluated experimentally on a genome-wide scale. Gabriel et al. document the off- and on-target activity of zinc-finger nucleases using lentiviral vectors to tag integration sites.
Gesehen am 05.07.2023